Note to the Spanish Pharmacopoeia; IX edition: bismuth subgallate - García Villanova, R.; Thomas, J.; Bosch, F. (Ars Pharmaceutica (Internet), 1966)
A gravimetric and complexometric technics of evaluation of bismuth subgallate has been revised. We recommended a complexometric technic, using EDTA and a potassium iodide, Pyrocatechol Viol and thiourea as indicator indifferently, in order to include it in the new Spanish Phamacopeia edition.